Runt‐related transcription factor 1 (Runx1) aggravates pathological cardiac hypertrophy by promoting p53 expression. Issue 16 (30th June 2021) - Zhang, Dianhong; Liang, Cui; Li, Pengcheng; Yang, Lulu; Hao, Zhengyang; Kong, Lingyao; Tian, Xiaoxu; Guo, Chenran; Dong, Jianzeng; Zhang, Yanzhou; Du, Binbin
Abstract: Cardiac hypertrophy and the resultant heart failure are among the most common causes of morbidity and mortality worldwide; thus, identifying the key factor mediating pathological cardiac hypertrophy is critically important for developing the strategy to protect against heart failure. Runx1 (Runt‐related transcription factor 1) acts as an essential transcription factor that functions in a variety of cellular processes including differentiation, proliferation, tissue growth and DNA damage response. However, relatively little is known about the role of Runx1 in heart, especially cardiac hypertrophy and heart failure. In the present study, we investigated the role of Runx1 in experimentally pathological cardiac hypertrophy. The in vitro model was induced by Ang II exposure to cultured neonatal rat cardiomyocytes, and the in vivo pathological cardiac hypertrophy models were induced by chronic pressure overload in mice. Runx1 expression is increased in heart tissues from mice with pressure overload–induced cardiac hypertrophy and in neonatal rat cardiomyocytes in response to Ang II stimulation. Moreover, knockdown of cardiac Runx1 alleviates the pressure overload–induced cardiac hypertrophy. Mechanistically, Runx1 activates the p53 signalling by binding to the p53 gene and promotes its transcription. Rescue experiments indicate that Runx1 promotes cardiac hypertrophy in a p53‐dependent manner. Remarkably, we demonstrated that Ro5‐3335 (a Runx1 inhibitor) acts as a potential therapeutic drug for treating pathological cardiac hypertrophy. In summary, we conclude that Runx1 is a novel mediator and therapeutic target for pathological cardiac hypertrophy.